Pelaksanaan Perjanjian Kredit pada Badan Usaha Milik Kampung (Bumkampung) Maju Bersama Desa Perawang Barat - Akmal, Saidul; Firmanda, Hengki; Hasanah, Ulfia (Peneliti.net, 2024)
The aim of this study is to analyze the implementation of credit agreements at the village-owned business entity (BUMKampung) Maju Bersama, West Perawang Village as well as efforts to resolve defaults in credit agreements between borrowers and the village-owned business entity (BUMKampung) Maju Bersama, West Perawang Village. The type of research used by the author is sociological legal research, namely examining applicable legal provisions and what happens in reality in society. The results of this research study stated that the implementation of the credit agreement at the village-owned business entity (BUMKampung) Maju Bersama, West Perawang Village, as well as efforts to resolve defaults in the credit agreement between the borrower and the village-owned business entity (BUMKampung) Maju Bersama, West Perawang Village, failed. The author in this discussion provides an explanation regarding the implementation of credit agreements at the village-owned business entity (BUMKampung) Maju Bersama, West Perawang Village as well as efforts to resolve defaults in the credit agreement between the borrower and the village-owned business entity (BUMKampung) Maju Bersama, West Perawang Village.